Ultrastructure of the adrenal gland of paca (Cuniculus paca, Linnaeus, 1766) in captivity - Filho, Sérgio Pinter Garcia; Martins, Leandro Luis; Marcusso, Paulo Fernandes; De Castro Sasahara, Tais Harumi; Machado, Márcia Rita Fernandes [UNESP] (Editora da Universidade Federal Rural do Semi-Arido - EdUFERSA, 2021)
Lowland paca (Cuniculus paca, Linnaeus, 1766) is a medium-sized rodent that belongs to the Brazilian fauna. Yet little information on its morphology is found in the specialized literature. Thus, the objective of the work was to study the morphology of the adrenal gland of paca by means of microscopic ultrastructure analysis. The adrenal gland secretes specialized substances in the body which promote biological functions of great importance and will provide valuable information to studies in comparative anatomy. Two (2) adult lowland pacas were used, male and female. Soon after death, the animals were positioned in the supine position; their abdominal cavities were opened by pre-retro umbilical and lateral incision followed by folding of the abdominal walls to expose the glands. The adrenal glands were removed; fragments were collected, fixed and prepared for ultrastructure observations using scanning electron microscopy and transmission electron microscopy techniques. It was observed that the adrenal glands of the paca have divisions as well as the limits of the cortical and medullary region, as well as the subdivisions of the glomerulosa, fasciculated and reticulated areas of the cortical region as in other rodents. An ultrastructure of cells and their components also showed a lot of similarity to that already demonstrated in different rodents.
Ultraestrutura da glândula adrenal de paca (Cuniculus paca, Linnaeus, 1766) em cativeiro
Keywords: Electron microscopy; Rodent; Suprarenal; Wild animals